Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/prep.201700180
|View full text |Cite
|
Sign up to set email alerts
|

Studying Crosslinker Chemical Structure Effect on the Tuning Properties of HTPB‐Based Polyurethane

Abstract: Hydroxyl terminated polybutadiene based polyurethanes with various crosslinker compounds have been prepared to investigate the effect of crosslinker content and structure on polyurethanes mechanical properties. Three various crosslinkers have been used in this study, including trimethylolpropane, triethanolamine, and boron trifluoride triethanolamine complex. The results established that increasing crosslinker content increased the polyurethane strength. Moreover, boron trifluoride triethanolamine complex show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Results indicated that the largest concentration of cross-linkers produced more distributed segment segregation and higher thermal stability. Cross-linking process in PU could be carried out through various methods, wherein low-molecular-weight compounds with more than two reactive hydrogens were used as cross-linkers, such as trimethylolpropane (TMP) and triethanolamine (TEA) [ 23 , 24 , 25 ]. Moreover, rhodamine chromophores have advantages of long wavelengths of excitation (greater than 550 nm) and emission (590 nm), good photostability, and high fluorescent quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that the largest concentration of cross-linkers produced more distributed segment segregation and higher thermal stability. Cross-linking process in PU could be carried out through various methods, wherein low-molecular-weight compounds with more than two reactive hydrogens were used as cross-linkers, such as trimethylolpropane (TMP) and triethanolamine (TEA) [ 23 , 24 , 25 ]. Moreover, rhodamine chromophores have advantages of long wavelengths of excitation (greater than 550 nm) and emission (590 nm), good photostability, and high fluorescent quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous study on the properties of the energetic materials, a novel catalyst has been prepared for AP thermal decomposition. In this regard, the unique properties of the GO and catocene have been applied to one catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…With the increment of the chemical cross‐linking in bonds, a decline in the thermal and mechanical properties of a corresponding polyurethane product is remarked as one of the direct effect of this material aging . Moreover, the presence of the allylic hydrogen atom with low association energy and type G hydroxyl groups has made HTPB a prospective substrate for radical oxidation reactions . On the other hand, thermal‐oxidation degradation is one of the most prominent problems in manufacturing of the polymeric products .…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, the presence of the allylic hydrogen atom with low association energy and type G hydroxyl groups has made HTPB a prospective substrate for radical oxidation reactions. 21,22 On the other hand, thermaloxidation degradation is one of the most prominent problems in manufacturing of the polymeric products. 23 This process directly affects the aging and shelf life of the polymeric ingredients and products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation